Association of extended interleukin-10 promoter haplotypes with disease susceptibility and manifestations in German patients with systemic lupus erythematosus. (April 2014) - Schotte, H; Willeke, P; Becker, H; Poggemeyer, J; Gaubitz, M; Schmidt, H; Schlüter, B
Objectives: Associations of interleukin-10 (IL-10) promoter single nucleotide polymorphisms (SNPs) and their haplotypes with systemic lupus erythematosus (SLE) are unclear. We extended the analysis of established proximal IL-10 promoter haplotypes to a more distal SNP with functional capacity. Methods: Two hundred and ten German caucasian SLE patients fulfilling the ACR criteria and 160 ethnically, age and sex matched controls were genotyped for IL-10 −2849 G > A, −1082 A > G, −819 T > C and −592 C > A. Haplotypes were reconstructed via a mathematical model, then allele and haplotype distributions were compared between patients and controls and patients with different disease manifestations. Results: We detected at −2849, −1082, −819 and −592 the four predominant haplotypes GGCC (22% in patients vs. 29% in controls), AGCC (24% vs. 21%), GACC (30% vs. 25%) and GATA (24% vs. 24%). GGCC was underrepresented in SLE patients, suggesting a protective effect (odds ratio (OR) 0.67, 95% confidence interval (CI) 0.48–0.94). AGCC was found significantly more frequently in patients with pathognomonic anti-dsDNA antibodies (26% vs. 15%; OR 1.98, 95% CI 1.04–3.75). As compared to patients with glomerulonephritis type V (WHO classification), the presumptive IL-10 high producer allele −2849 G was found significantly more often in patients with GN type III/IV (93% vs. 60%; OR 8.7, 95% CI 1.59–47.15). Conclusion: Our data confirm that the complexity of the IL-10 promoter evokes the need for a meticulous analysis of its haplotypic structure in order to specify disease associations, particularly under functional aspects, thereby shedding light on the pathophysiology of SLE.